Karakteristik Fisik Kimia Dan Organoleptik Cookies Dengan Campuran Tepung Mocaf Dan Tepung Kacang Tunggak (Vigna Unguiculata) - Steffie Susanto Adjie (BiSTeK Pertanian, 2022)
Cookies are one type of snack that is very popular with people both in city and village areas. Cookies are a type of biscuit made from soft, crispy dough and when broken the cross section looks less dense textured. In general, the stage of making cookies consists of mixing, printing and baking. Basically, making cookies uses low protein flour. The high demand for wheat flour has increased the volume of wheat imports from year to year so as to reduce dependence on consumption of wheat flour by utilizing local food ingredients. Mocaf and cowpea flour can be used for replace wheat flour in making cookies. Mocaf is flour made from fermented cassava. Cowpea flour is flour made from milled cowpea.